Effect of Financial Incentives on Employee Performance in Nepalese Commercial Bank - Karmacharya, Purnima (Nepalese Journal of Economics, 2025)
The study examines the effect of financial incentives on employee performance in Nepalese commercial bank. Employee performance is selected as the dependent variables. Similarly, the selected independent variables are bonus, retirement benefit, stock option, salary and employee welfare benefit. The primary source of data is used to assess the opinions of respondents regarding bonus, retirement benefit, stock option, salary and employee welfare benefit on employee performance in Nepalese commercial bank. The study is based on primary data of 120 respondents. To achieve the purpose of the study, structured questionnaire is prepared. The correlation and multiple regression models are estimated to test the significance and effect of financial incentives on employee performance in Nepalese commercial bank. The study showed that bonus is positively correlated to employee performance working at bank. It indicates that bonus leads to an increase in performance of employees. Likewise, retirement benefit is positively correlated to performance of employees working at bank. It indicates that retirement benefit has a positive impact on performance of employees. Further, stock option is positively correlated to performance of employees working in bank. It indicates that stock option leads to an increase in performance of employees. Additionally, salary and employee welfare benefit also demonstrate positive correlations with employee’s performance working at bank, indicating higher the salary and employee welfare benefit, higher will be the employee performance.